tutorial02soln
tutorial02soln
Solutions: An argument is valid if whenever the premises are true, the conclusion is also true.
We begin by analysing the logical form of the argument. Then we construct a corresponding truth
table and examine it. If in every row of the table that has value true for each premise, the value
for the conclusion is also true, we know that the argument is valid.
1. Let J stand for “John is telling the truth”, B stand for “Bill is telling the truth”, and S stand
for “Sam is telling the truth”. Then:
J ∨B premise 1
¬S ∨ ¬B premise 2
Therefore, J ∨ ¬S conclusion
1
JM PM JC PC ¬( JM ∧ PM) PM ∨ PC JM PC
T T T T F T T T TTT T T
T T T F F T T T TTF T F
T T F T F T T T TTT T T
T T F F F T T T TTF T F
T F T T T T F F FTT T T
T F T F T T F F FFF T F
T F F T T T F F FTT T T
T F F F T T F F FFF T F
F T T T T F F T TTT F T
F T T F T F F T TTF F F
F T F T T F F T TTT F T
F T F F T F F T TTF F F
F F T T T F F F FTT F T
F F T F T F F F FFF F F
F F F T T F F F FTT F T
F F F F T F F F FFF F F
We conclude that the argument is valid.
Note: A solution that does not use the variable JC is also correct, since it is not used in the
premises or the conclusion.
JM PM PC ¬( JM ∧ PM) PM ∨ PC JM PC
T T T F T T T TTT T T
T T F F T T T TTF T F
T F T T T F F FTT T T
T F F T T F F FFF T F
F T T T F F T TTT F T
F T F T F F T TTF F F
F F T T F F F FTT F T
F F F T F F F FFF F F
¬(a ∨ b) ∧ ¬c de Morgan’s
eqv ¬((a ∨ b) ∨ c) shorthand
eqv ¬(a ∨ b ∨ c)
2
Solutions:
¬(a ∧ b) ∨ c de Morgan’s
eqv (¬a ∨ ¬b) ∨ c associative
eqv ¬a ∨ (¬b ∨ c) double negation
eqv ¬a ∨ (¬b ∨ ¬¬c) de Morgan’s
eqv ¬a ∨ ¬(b ∧ ¬c)
¬(P ∨ Q) ∨ ¬Q de Morgan’s
eqv (¬P ∧ ¬Q) ∨ ¬Q commutative
eqv ¬Q ∨ (¬P ∧ ¬Q) commutative
eqv ¬Q ∨ (¬Q ∧ ¬P ) absorption
eqv ¬Q
¬A ∧ ¬(B ∧ C) de Morgan’s
eqv ¬A ∧ (¬B ∨ ¬C) distributive
eqv (¬A ∧ ¬B) ∨ (¬A ∧ ¬C) de Morgan’s twice
eqv ¬(A ∨ B) ∨ ¬(A ∨ C)
1. a → b and a ∧ b
Solutions:
Let a = b = f alse. Then a → b = F → F = T but a ∧ b = F ∧ F = F . The two expressions
are not equivalent.
2. a → b and ¬a → ¬b
Solutions:
Let a = true and b = f alse. Then a → b = T → F = F but ¬a → ¬b = ¬T → ¬F = F →
T = T . The two expressions are not equivalent.
3. (a → b) ∧ (b → c) and (a ∧ b) → c
Solutions: Let a = true and b = c = f alse. Then (a ∧ b) → c = (T ∧ F ) → F = F → F = T
but (a → b) ∧ (b → c) = (T → F ) ∧ (F → F ) = F ∧ T = F . The two expressions are not
equivalent.
3
• Q, if P .
• P is a sufficient condition for Q.
• Q is a necessary condition for P .
Solutions: Notice the direction of implication with:
• “A, if B”: A ← B
• “A only if B”: A → B
• “A if and only if B”: A ↔ B equivalently (A ← B) ∧ (A → B)
Analyse the logical forms of each of the following English statements.
1. Mary will sell her house only if she can get a good price and find a nice apartment.
Solutions: Let S stand for “Mary will sell her house”, P stand for “Mary can get a good price”,
and A stand for “Mary can find a nice apartment”. Then
S → (P ∧ A)
2. Having both a good credit history and an adequate down payment is a necessary condition for
getting a mortgage.
Solutions: Let H stand for “one has good credit history”, D stand for “one has adequate down
payment”, and M stand for “one gets a mortgage”. Then
M → (H ∧ D)
(S → ¬D) ∧ (¬S → D) or S ↔ ¬D
In some literature, you may also see the following interpretation of “unless”:
¬D → S or D∨S
4. Being enrolled full time and demonstrating financial need is a sufficient condition for applying
for assistance.
Solutions: Let E stand for “one is enrolled full time”, N stand for “one demonstrates financial
need”, and A stand for “one can apply for financial assistance”. Then
E∧N →A